1977
DOI: 10.1002/bjs.1800640212
|View full text |Cite
|
Sign up to set email alerts
|

Protein turnover in patients before and after elective orthopaedic operations

Abstract: Whole body protein turnover was measured in 11 patients before and after elective orthopaedic operations be giving 15N-glycine orally every 4 hours for 32 hours. The patients were maintained throughout on a constant protein intake. In 2 control subjects a comparison was made between intermittent dosage and continuous infusion of 15N-glycine for the estimation of total protein turnover. With intermittent dosage the 15N abundance in urinary urea reached a constant level after about 24 hours. Rates of total prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2
1

Year Published

1977
1977
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(20 citation statements)
references
References 11 publications
0
17
2
1
Order By: Relevance
“…The absence of any marked difference in 3-methylhistidine excretion in the orthopaedic surgery, hyperketonaemic injury and skin-graft groups therefore suggests that increased muscleprotein breakdown is not responsible to any appreciable extent for the higher nitrogen excretion in the first two groups, and that this must therefore result from an increased catabolism of non-myofibrillar proteins andlor decreased protein synthesis. Evidence from other sources suggests that a decrease in protein synthesis rather than increased breakdown of protein may be responsible for the ele&ed postoperative loss of nitrogen after moderately severe elective surgery (O'Keefe et al, 1974;Crane et al, 1977). Animal experiments also support the view that muscle-protein mass is regulated primarily through alterations in the rate of protein synthesis and that increases in breakdown rate only rarely play a role (Milward, Garlick, Nnanyelugo & Waterlow, 1976).…”
Section: Discussionmentioning
confidence: 87%
“…The absence of any marked difference in 3-methylhistidine excretion in the orthopaedic surgery, hyperketonaemic injury and skin-graft groups therefore suggests that increased muscleprotein breakdown is not responsible to any appreciable extent for the higher nitrogen excretion in the first two groups, and that this must therefore result from an increased catabolism of non-myofibrillar proteins andlor decreased protein synthesis. Evidence from other sources suggests that a decrease in protein synthesis rather than increased breakdown of protein may be responsible for the ele&ed postoperative loss of nitrogen after moderately severe elective surgery (O'Keefe et al, 1974;Crane et al, 1977). Animal experiments also support the view that muscle-protein mass is regulated primarily through alterations in the rate of protein synthesis and that increases in breakdown rate only rarely play a role (Milward, Garlick, Nnanyelugo & Waterlow, 1976).…”
Section: Discussionmentioning
confidence: 87%
“…It seemed important, for both theoretical and practical reasons, to find out which mechanism accounted for Cuthbertson's catabolic loss. The first attempts to study this problem suggested that surgical trauma caused a decrease in protein synthesis (O'Keefe et al 1974;Crane, Picou, Smith & Waterlow, 1977). Hartig and co-workers found that the cumulative excretion of 15N after the administration of ["5N]glycine was twice as great in patients after cholecystectomy as in controls (Hartig, Faust, Czarnetzki, Putziger & Wetzel, 1980).…”
Section: The Effects Of Injury and Infectionmentioning
confidence: 99%
“…The surgical shown that this "catabolic" loss of nitrogen appeared to be a procedures the infants underwent are listed by diet group in consequence of a reduction in whole body protein synthesis Table 1. rather than an increase in proten breakdown (1)(2)(3). Amino acids Whole body N turnover was studied using the approach dewhich are not used for synthesis are then degraded resulting in scribed by Picou and Taylor-Roberts (8) and modified by Penan increased urea formation and thus, an increase in urinary charz et al (7).…”
Section: Through Visceral Protein (Pediatr Res 20: 32-35 1986)mentioning
confidence: 99%
“…Registration for this examination will extend from October 1, 1985, until January 3 1,1986. To request an application, please contact the Board office at the address listed below.…”
Section: Announcementmentioning
confidence: 99%